As inter-relações: disfagia, nutrição e fonoaudiologia em idosos - Saraiva, Andréa Osório Machado (Universidade do Vale do Rio dos Sinos, 2012)
With the change of age and demographic profile of the population, some alterations are noted, concerning nutritional and phonoaudiological status, on the aging process. The elderly with dysphagia becomes more fragile, and may develop complications, such as aspiration pneumonia and changes in food intake, which can compromise his health. Identify the associations of dysphagia with nutritional and phonoaudiological aspects and factors that affect the older adults. It is a descriptive bibliographic survey, of documentary base, through analysis and synthesis of indexed journal’s articles (Medlina; Lilacs Scielo; e, PubMed), technical books and publications. 38 articles were selected to perform this study. This survey concluded the importance of treating the old age with dysphagia early, so that major damage to their nutritional and hydration state can be avoided. Therefore, at the moment the diagnosis is confirmed, the actions of a multidisciplinary team for dysphagia triage are essential: physician; nutritionist; audiologist; nurse; occupational therapist; psychologist; which are of fundamental importance on general treatment of the health of the elderly with dysphagia.
Keywords: Disfagia; Idoso; Nutrição; Terapia nutricional; Fonoaudiologia; Dysphagia; Older adults; Nutrition; Nutritional support; Phonoaudiology